Dose-response relationship of resistance training in older adults: a meta-analysis - Steib, Simon; Schöne, Daniel; Pfeifer, Klaus (Medicine and science in sports and exercise, 2010)
Purpose: - The purpose of this study was to determine the dose-response relationship of resistance training (RT) to improve strength and function in older adults. - Methods: - A systematic literature search was performed in relevant databases and study reference lists to identify randomized controlled trials. Randomized controlled trials comparing the effects of different doses of strength training in older people (65 yr and older) on strength and functional outcomes were eligible. Two independent reviewers decided on study inclusion, extracted data, and assessed methodological quality. Standardized mean difference (SMD) and 95% confidence intervals (CI) were calculated for relevant outcomes and pooled using a random-effects model. - Results: - Twenty-nine trials with a total of 1313 subjects (mean age = 65-81 yr) are summarized in this review. Trials comparing different training intensities show strong effects of progressive resistance training (PRT) on maximal strength in a dose-dependent manner, with high-intensity (HI) PRT being more effective compared with moderate (MI)- and low-intensity (LI) PRT (SMD [HI vs LI] = 0.88, 95% CI = 0.21-1.55; SMD [HI vs MI] = 0.62, 95% CI = 0.22-1.03). PRT was also successful for improving functional outcomes, but gains were independent of training intensity. Power training (PT) was more effective for improving muscle power (SMD [PT vs PRT] = 1.66, 95% CI = 0.08-3.24) and functional outcomes than PRT. There was only little information available on training volume and frequency. - Discussion: - Higher training intensities are superior to lower intensities for improving maximal strength but not necessarily for functional performance of older adults. PT has shown to be a particularly effective method for enhancing muscle power and functional performance. More research is necessary to identify the effect of different training volumes and frequencies and the dose-response relationship for very old and frail populations.
Gesehen am 13.07.2022